Bridging policy and practice: The implementation of inventory accounting standards in Indonesian local governments - Marsus, Soffan; Yasni, Raynal; Fajarianti, Muliani Sulya; Arianto, Agung; Sustiyo, Joko (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Inventory accounting plays a critical role in public sector financial management, supporting transparency, asset control, and budget accountability. This study examines the challenges associated with implementing inventory accounting standards in Indonesian local governments, with a particular focus on inventory recording, classification, and governance. Using an interpretive qualitative approach, the research draws on document analysis of national and international accounting standards and focus group discussions with government accounting practitioners. The findings reveal persistent difficulties in integrating financial and inventory systems, notably due to discrepancies in classification codes, incomplete asset handover documentation, and fragmented regulatory frameworks. The transition to digital inventory management remains hindered by limited technical capacity, system fragmentation, and inconsistent application of valuation methods, especially the use of first-in, first-out (FIFO) and first-expired, first-out (FEFO) approaches in the health and procurement sectors. These issues contribute to inefficiencies in financial reporting and elevate audit risks. The study highlights the need for regulatory harmonization, improved interdepartmental coordination, and stronger governance mechanisms to enhance compliance and transparency. The adoption of integrated digital tracking systems and standardized reporting procedures is also recommended to reduce inconsistencies and improve audit readiness. This research contributes to the literature by offering practical insights into regulatory misalignment and proposing strategies to improve inventory management in local government.